DESIGNING UI/UX FOR A MEDITERRANEAN DIET APP TO MINIMIZE TYPE 2 DIABETES RISK - Salam, Farah Danisha; Pamungkas, Endang Wahyu (Jurnal Teknik Informatika (Jutif), 2024)
The industrial revolution has had a significant impact in health field, where the crucial disease in Indonesia is Type 2 Diabetes Mellitus (T2DM). One of the effective ways to minimize the increase in T2DM is by developing a diet application using Mediterranean diet Method. The Mediterranean diet involves controlling certain types of foods and beverages, characterized by high intake of fruits, vegetables, whole grains, nuts, legumes, moderate consumption of fish, low intake of red/processed meat, and low intake of high-fat dairy products. In this research and design, the Author applied User Centered Design (UCD) method, which encompasses User Interface (UI) and User Experience (UX). The author also applied the UX law (Hick’s Law, Law of Proximity, dan Aesthetic-usability Effect) on designing the user interface. This article included a A/B Testing and System Usability Scale (SUS) result that showed an interesting findings, where the design that achieved a higher success rate had a lower user satisfaction score and vice versa. However, both designs have an acceptable score and C grade.